„Wędrujące pojęcia”. Koncepcja Mieke Bal – przykład inter- czy transdyscyplinarności? - Tabaszewska, Justyna (Instytut Kultury Europejskiej UAM w Gnieźnie oraz Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2013)
The notions of inter- and transdisciplinarity represent categories which the humanities frequently resort to in the discourse, but which remain difficult to define. The attempts to do so are most often associated with subscribing to one of the possible models of interpreting relationships between individual disciplines of science. Mieke Bal’s concept of transdisciplinarity, which this paper discusses, envisages a framework where the privileged form of formulating scientific concepts would be in research practice that is rooted not only in the methodologies of individual sciences but most of all in the everyday practices and experiences.
“THE WANDERING NOTIONS”. THE CONCEPTS OF MIEKE BAL – AN INSTANCE OF INTER- OR TRANSDISCIPLINARITY?
Summary: In her Travelling Concepts in the Humanities: A Rough Guide, Mieke Bal argues that the contemporary phenomenon of transdisciplinarity may be described by means of the metaphor of wandering and migrating notions which, relocating from one discipline into another, change their original meaning. Nevertheless, the motion is not unidirectional, the notions and concepts ‘circulate’ between various fields of the humanities, not merely pass from one into the other. They evolve while functioning within a given discourse, transform their original meanings so that they may better describe certain phenomena. Not infrequently, they return, transformed, into their initial domain where they turn out to be even more useful for the change. Thus, the continually migrating concepts may form a network of unique connections without damage to the methodology and specificity of particular fields. Visuality is one of such ‘wandering notions’. Although Bal does not address it in that particular book, tracing the course of changes that the visuality underwent is a good starting point in determining the opportunities and risks resulting from the adoption of such framework of transdisciplinarity. With visual studies recognised as transdisciplinary studies, it becomes possible to disentangle oneself from the oppositional definitions of text and image
Keywords: INTERDISCIPLINARITY; TRANSDISCIPLINARITY; VISUALITY; IMAGE; MISE-EN-SCENE